The use of intercultural interpreter services at a pediatric emergency department in Switzerland - Buser Sina; Gessler Noemi; Gmuender Myriam; Feuz Ursula; Jachmann Anne; Fayyaz Jabeen; Keitel Kristina; Brandenberger Julia (BMC Health Services Research, 2022)
Abstract The aim of our study was to analyze the use of interpreter services and improve communication during health encounters with families with limited language proficiency (LLP) at the pediatric emergency department (ED) of the University Hospital of Bern. This study is a pre- and post-intervention study analyzing the use of interpreter services for LLP families. All families originating from a country with a native language other than German, English or French presenting to the ED were eligible to participate in the study. If they agreed to participate, the language proficiency of the caregiver present during the health encounter was systematically assessed during a phone interview within a few days after the consultation, using a standardized screening tool. If screened positive (relevant LLP), a second phone interview with an interpreter was conducted. Further variables were extracted including nationality, age, gender and date of visit using administrative health records. To increase the use of interpreter services, a package of interventions was implemented at the department during 3 months. It consisted of: i) in person and online transcultural teaching ii) awareness raising through the regular information channels and iii) the introduction of a pathway to systematically identify and manage LLP families. The proportion of LLP families who received an interpreter was 11.0% (14/127) in the pre-intervention period compared to 14.8% (20/135) in the post-intervention period. The interpreter use was therefore increased by 3.8% (95% CI − 0.43 to 0.21; p = 0.36). The assessed level of language proficiency of caregivers differed from the self-reported level of language proficiency. Of the study participants in the interview whose language proficiency was screened as limited, 77.1% estimated their language proficiency level as intermediate. More than half of the LLP families who did not receive an interpreter and participated in the interview reported, that they would have liked an interpreter during the consultation. Conclusions: Interpreter services are largely underused during health encounters with LLP families. Relying on caregivers´ self-assessed language proficiency and their active request for an interpreter is not sufficient to ensure safe communication during health encounters. Systematic screening of language proficiency and standardized management of LLP families is feasible and needed at health care facilities to ensure equitable care. Further studies are needed to analyze personal and institutional barriers to interpreter use and find interventions to sustainably increase the use of interpreter services for LLP families.